Analysis of the influence of hadith methodology in the scientific method development: A study of the biography and writings of Ibn al-Haytham - Permana, Bryan Pandu; Miftakhussurur; Hubbur, AA (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2025)
This study explores the influence of Hadith methodology on the development of science through the study of the biography and works of Ibn al-Haytham. The research aims to identify the scientific methodologies used in Hadith studies and analyze their relevance and impact on Ibn al-Haytham's scientific approach. The Methods that used by this reseach are by examining comparative study of both methods with analyze from timeline background from historical sources and Ibn al-Haytham’s books. The study reveals significant parallels between the rigorous validation processes in Hadith methodology and the methods employed by Ibn al-Haytham in his scientific inquiries. The findings suggest that the principles of verification and validation in Hadith studies may have influenced the development of systematic scientific methods in science particularly in the works of Ibn al-Haytham. This research contributes to a deeper understanding of the interconnectedness between Islamic religious scholarship and the evolution of scientific thought.